Digital Literacy of Netizens on Social Media (Content Analysis of Twitter @clickunbait Period January 1 - February 28, 2019) - Alif Arfayano Tegar Herbowo; Marfuah Sri Sanityastuti (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
One of the issues with modern media, including Twitter, is Clickbait. Clickbait seems to be the answer for online media, especially for news reporting. By utilizing a grandiose title, Clickbait allows online media to create content that will draw internet users. in order to boost the number of people that read the news on their website. Twitter is a social media platform that some businesses can use to spread their news. The media can easily and quickly spread their news by using Twitter. For whatever reason, Clickbait violates The Ethics Code of Journalistic. It happens when news stories have click-bait headlines that have little to do with the actual content. As a result, @Clickunbait emerges and seems to educate internet users. giving internet users the knowledge necessary to understand digital literacy so they can process the information they accept.Keywords: Twitter, Digital Literacies, Clickbait, Netizens.